Practical pediatric and adolescent gynecology - Hillard, Paula Adams (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, A John Wiley & Sons, Ltd., Publication, 2013)
The gynecology of young girls and teenagers provides exacting challenges. Intimate examination can be daunting for the patient, and the balance between parental permission and patient privacy shifts as menstruation and sexual activity begins. This practical book provides a nuts and bolts approach to the gynecological examination and management of young patients.
Prepubertal girls -- Introduction -- Initial assessment -- Prepubertal girls: symptoms and signs -- Ambiguous genitalia in the neonate and infant -- Vaginal discharge and odor -- Vaginal bleeding -- Ovarian masses -- Prepubertal girls: gynecologic conditions -- Labial adhesions -- Pediatric vulvovaginitis -- Sexual abuse -- Concerns in prepubertal girls and in adolescents -- External genitalia -- Normal hymen and hymenal variations -- Vulvar signs and symptoms -- Vulvar lichen sclerosus -- Accidental trauma -- Female genital mutilation -- Puberty -- Normal puberty -- Precocious puberty -- Delayed puberty -- Adolescent girls -- Adolescent health -- Initial assessment: consultation with an adolescent girl -- Confidentiality -- Legal issues -- Adolescent sexuality -- Adolescent preventive care for healthy teens -- Weight -- The female athlete -- Immunizations -- Substance abuse: screening and brief intervention -- Suicidal ideation and self-harm: screening -- Healthcare for lesbian, bisexual, and transgender adolescents -- Developmental delay -- Menstrual health -- The gynecologic exam -- Sexually-transmitted disease screening -- Pregnancy prevention and options -- Unintended pregnancy: options and counseling -- Contraceptive counseling -- Contraception -- Adolescent girls: symptoms and signs -- Hirsutism -- The breast -- Vaginal discharge -- Pelvic masses -- Gynecologic pain -- Amenorrhea -- Abnormal uterine bleeding -- Premenstrual syndrome/premenstrual dysphoric disorder and mood disorders -- Adolescent girls: gynecologic conditions -- Vulvovaginal conditions -- Sexually-transmitted diseases -- Dysmenorrhea -- Congenital anomalies -- Ectopic pregnancy -- The ovaries -- Endometriosis -- Polycystic ovary syndrome -- Pelvic inflammatory disease -- Gonadal dysgenesis -- Sexual assault and date rape -- Essential information -- Useful web resources for adolescents, their parents/caregivers, and clinicians.
Includes bibliographical references and index.
Online resource; title from resource home page (ebrary, viewed on April 11, 2014).
Keywords: Pediatric gynecology; Genital Diseases, Female; Gynecological Examination -- methods; Adolescent; Child; Infant; MEDICAL -- Pediatric Emergencies; Pediatric gynecology; Electronic books; Electronic books